The multiculturalist problematic in the age of globalized capitalism - San Juan, Epifanio (Social justice, 2000)
Part of a special section on race, class, and state crime. The writer contends that the current controversy regarding multiculturalism as political doctrine or pedagogical stance has shifted beyond national borders in line with the explosion of ethnic and racially motivated conflicts in Europe, Africa, and around the world. He considers certain questions that epitomize the pros and cons of the debate on multiculturalism in the continuing “Culture Wars,” and he discusses different varieties of multiculturalisms. Finally, he concludes that only a creative, militant historical-materialist analysis and critique can enable distinction and evaluation of the overdetermined trajectories and tendencies in the raging “PC/culture wars,” from whose effects nobody is immune.